GREETING MESSAGE - INC 3 Nursing (UNEJ e-Proceeding, 2017)
Bismillahirrohmanirrohim Assalamualaikum Wr Wb Good morning and best wishes The Honorable, Rector of University of Jember The Honorable, Dean School of Nursing, University of Jember The Honorable, All Speaker of the International Nursing Conference The Honorable, Guests The Honorable, Conference Committee Dear All, All Participants of the conference Thank God we praise the presence of Allah SWT, because of the blessing and grace, we all can be present in this place, in order to attend the International Nursing Conference. Solawat and greetings may still be delegated to the Great Prophet Muhammad SAW. Ladies and Gentlemen, As the beginning of this speech, I would like to say welcome to the third international nursing conference, with the theme "Community Health Empowerment: Step Up Action Attaining Sustainable Development Goals". Good development for the community is sustainable development. Sustainable development is a development aimed at improving the quality of life of people around the world, both from present and future generations, without exploiting the use of natural resources that exceeds the capacity as well as capacity of the earth. This goal can be achieved through four elements of sustainable development objectives: (1) Economic growth and justice; (2) Social development; (3) Conservation of natural resources (environmental protection); (4) Good governance. These four elements are mutually supporting each other, creating relevant and sustainable development goals. At the United Nations (UN) Conference held in Rio de Janeiro (Brazil) in June 2012, a sustainable development agenda called Sustainable Development Goals (SDGs) was discussed. SDGs are a set of objectives, targets, and indicators of sustainable development that are universal. SDGs are a continuation and expansion of the Millennium Development Goals (MDGs) that have been undertaken by countries since 2001 until the end of 2015. At a summit meeting at the UN headquarters in September 2015, 193 UN member states agreed to make SDGs the framework of the political development and policy agenda over the next 15 years from 2016 to 2030. Governments in every UN member country, whether rich or poor, both developed and developing countries, have the responsibility to implement SDGs to achieve SDGs. SDGs consist of 17 goals and 169 targets, covering various Sustainable development issues. Of the 17 objectives of the SDGs, one of them is on Education and Health. How is the implementation of the SDGs in our country and the Asian countries? To answer that question, then for the next 2 days starting from today on 4-5 November 2017 at Royal Hotel, we will discuss the implementation of SDGs with speakers from 5 countries namely: iii 1. Prof. Dr. Nursalam,M.Nurs., (HONS).Chairman of Indonesian National Nurses Association (East Java Region) (Indonesia). 2. Prof. Ching-Min Chen from National Cheng Kung University (Taiwan) 3. Prof. Violeta Lopez from National University of Singapore (Singapore) 4. Associate Prof. Dr. Wandee Sutarangsee from Prince of Songkla university (Thailand) 5. Br. Noel M. Tecson, SVD, RN, MSNfromUniversity of San Carlo (Philipines) 6. Ns. Tantut Susanto, Ph.D. from University of Jember (Indonesia) Ladies and Gentlemen This conference is attended by students, health department delegates, academics, hospital and community clinic practitioners with a total of 193 participants. This event can be held because of the support and efforts of all parties. Therefore, I would like to thank the Rector of University of Jember, Head of School of Nursing- University of Jember, Indonesian National Nurses Association (INNA) or PPNI, Royal Hotel and all the committees who have worked hard to carry out this activity. I also thank to the sponsors who have worked with us so that this event run as expected. Amen. We as the committee, apologize if there is anyinconvenience during this event. Our hope that this activity can increase our knowledge that benefits all of us. Amen. Before I end my speech, I want to say "when we interpret that today is an ordinary day, then we will come out of this room as an ordinary people, but when we interpret that today is a very extraordinary day, then we will come out of this room as a very wonderful person ". Finally, please enjoy this conference, may Allah SWT always gives blessings to all of us. Amen Wassalamualaikum Wr. Wb. Chairperson Ns. Siswoyo, M. Kep.